Circulating hypervirulent Marek’s disease viruses in vaccinated chicken flocks in Taiwan by genetic analysis of meq oncogene - Cheng, Ming-Chu; Lai, Guan-Hua; Tsai, Yi-Lun; Lien, Yi-Yang (PloS one, 2024)
Marek’s disease (MD) is an important neoplastic disease caused by serotype 1 Marek’s disease virus (MDV-1), which results in severe economic losses worldwide. Despite vaccination practices that have controlled the MD epidemic, current increasing MD-suspected cases indicate the persistent viral infections circulating among vaccinated chicken farms in many countries. However, the lack of available information about phylogeny and molecular characterization of circulating MDV-1 field strains in Taiwan reveals a potential risk in MD outbreaks. This study investigated the genetic characteristics of 18 MDV-1 strains obtained from 17 vaccinated chicken flocks in Taiwan between 2018 and 2020. Based on the sequences of the meq oncogene, the phylogenetic analysis demonstrated that the circulating Taiwanese MDV-1 field strains were predominantly in a single cluster that showed high similarity with strains from countries of the East Asian region. Because the strains were obtained from CVI988/Rispens vaccinated chicken flocks and the molecular characteristics of the Meq oncoprotein showed features like vvMDV and vv+MDV strains, the circulating Taiwanese MDV-1 field strains may have higher virulence compared with vvMDV pathotype. In conclusion, the data presented demonstrates the circulation of hypervirulent MDV-1 strains in Taiwan and highlights the importance of routine surveillance and precaution strategies in response to the emergence of enhanced virulent MDV-1.